COVID-19 pandemic and its impact on peer review speed of anesthesiology journals: An observational study - Bikram Kishore Behera; Rakesh Vadakkethil Radhakrishnan; Chitta Ranjan Mohanty; Snigdha Bellapukonda (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Publication of a scientific article in a reputed journal is an uphill task that demands a significant amount of time and effort from the author and editorial team. It is a matter of great enthusiasm for all prospective researchers to know whether this daily evolving publication load of articles during this pandemic had changed the journal's inherent peer review or publication process. We aimed to compare the peer review speed of anesthesiology journal articles published during pandemic (2020) to the previous year and to analyze various factors affecting peer review speed. Material and Methods: Overall, 16 anesthesiology journals indexed in MEDLINE database were retrospectively analyzed. A set of 24 articles published in 2019 of the included journals were selected from each journal for control and a set of 12 articles published between January to September 2020 was selected for comparison. Time taken for acceptance and publication from the time of submission was noted. Peer review timing was calculated and its relationship with h-index, continent of journal origin and article processing charges were evaluated. Results: The median peer review time in 2019 and 2020 were 116 (108-125) days and 79 (65-105.5) days, respectively. There was a 31.8% decrease (P = 0.0021) in peer review time of all articles in 2020 compared to 2019. The median peer review timings of COVID-19 articles were 35 (22-42.5) days. A 55.6% decrease was noted in peer review time of COVID-19 articles compared to non-COVID-19 articles in 2020. There was a significant correlation between peer review time and h-index (r = 0.558, P = 0.024). There was no significant difference in peer review timing of journals with or without article processing charge (P = 0.75) and between journals from different continents (P = 0.56). Conclusion: Anesthesiology journals managed to curtail their turnaround time for peer review during the pandemic compared to previous year. Journal with higher h-index had longer peer review time. The option for articles processing charge and continent of publishing journal had no impact on peer review speed.